Faktor-Faktor Yang Mempengaruhi Penghindaran Pajak Dampak Sebelum Dan Selama Pandemi Covid-19 Pada Perusahaan Consumer Non Cyclical Di Bursa Efek Indonesia - Ani Kusbandiyah; Eko Priyanto; Purnadi Purnadi; Rina Mudjiyanti (ITB AAS INDONESIA, 2023)
The purpose of this study is to examine and find empirical evidence of the influence of political connections, profitability, managerial ownership, and institutional ownership on tax avoidance and to determine differences in tax avoidance before and during the Covid-19 pandemic in Non-Cyclical Consumer companies on the Indonesia Stock Exchange for the 2018-2021 period. Based on sample selection using purposive sampling, 86 sample data were obtained. The analytical method used was multiple linear regression and Wilcoxon signed rank test. The results show that political connections have no effect on tax avoidance, ROA has a positive effect on tax avoidance, managerial ownership and institutional ownership have no effect on tax avoidance in non-cyclical consumer companies listed on the IDX. The results of the Wilcoxon signed rank test show that there are differences in tax avoidance before and during the Covid-19 pandemic. The CETR value before the Pandemic is greater than the CETR value during the Pandemic. This means that there is an increase in tax avoidance during the Pandemic because if the CETR value is getting smaller, it means that the increase in tax avoidance is increasing. Keywords: CETR, Political Connections, ROA, Managerial and Institutional Ownership